Intergroup Conflict Resolution in Markum Village and Tupoplyo Village Okbab District, Mountain Bintang District - Etius Kasipka; Sri Suwartiningsih (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
Conflicts in the Okbab District of the Bintang Mountains district still often occur between community groups. In 1 year there can be several conflicts which are sometimes caused by things that are not clear. Based on these facts, this study aims to describe conflict management carried out on groups in conflict in Okbab District, Bintang Mountains Regency. This research was conducted by collecting data through library research, field research in the form of observation, in-depth interviews and document research. The results of this study indicate that conflict resolution is carried out starting from the conflict actors and also the local government so that resolution occurs. The youths were talked to and given the opportunity to improve themselves and their relationship with the conflicting youth groups, which occurred between the community group of Kampung Markum and the community of the village of Tupoplyom. The District Government and the village government mediate so that this problem reaches a point of peace. In this case, the government, which has a role as a facilitator, has succeeded in resolving conflicts between these youth groups little by little. From this research, it was found that several efforts were made by the government, both the district government and the village government in dealing with the problem of conflict between these youth groups.